Dual-side etched microstructured semiconductor neutron detectors - Fronk, Ryan G. (Kansas State University, 2017)
Interest in high-efficiency replacements for thin-film-coated thermal neutron detectors led to the development of single-sided microstructured semiconductor neutron detectors (MSNDs). MSNDs are designed with micro-sized trench structures that are etched into a vertically-oriented pvn-junction diode, and backfilled with a neutron converting material, such as ⁶LiF. Neutrons absorbed by the converting material produce a pair of charged-particle reaction products that can be measured by the diode substrate. MSNDs have higher neutron-absorption and reaction-product counting efficiencies than their thin-film-coated counterparts, resulting in up to a 10x increase in intrinsic thermal neutron detection efficiency. The detection efficiency for a single-sided MSND is reduced by neutron streaming paths between the conversion-material filled regions that consequently allow neutrons to pass undetected through the detector. Previously, the highest reported intrinsic thermal neutron detection efficiency for a single MSND was approximately 30%. Methods for double-stacking and aligning MSNDs to reduce neutron streaming produced devices with an intrinsic thermal neutron detection efficiency of 42%. Presented here is a new type of MSND that features a complementary second set of trenches that are etched into the back-side of the detector substrate. These dual-sided microstructured semiconductor neutron detectors (DS-MSNDs) have the ability to absorb and detect neutrons that stream through the front-side, effectively doubling the detection efficiency of a single-sided device. DS-MSND sensors are theoretically capable of achieving greater than 80% intrinsic thermal neutron detection efficiency for a 1-mm thick device. Prototype DS-MSNDs with diffused pvp-junction operated at 0-V applied bias have achieved 53.54±0.61%, exceeding that of the single-sided MSNDs and double-stacked MSNDs to represent a new record for detection efficiency for such solid-state devices.
Keywords: Neutron; Radiation; Neutron detection; Radiation detection